2022
DOI: 10.1021/acssuschemeng.1c08133
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated MAX Phases for Photoelectrochemical Hydrogen Evolution

Abstract: Photoelectrochemical generation of hydrogen from water is considered to be the most appealing solution for the replacement of fossil fuels as a source of energy. For this reason, the study of novel and affordable materials with high energy conversion efficiencies is currently a crucial objective for the scientific community. Chemical modification of two-dimensional (2D) and layered materials, such as fluorination, can play a decisive role in tuning the properties for energy-related applications, as it was docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Recent studies have taken one step back, looking into the fundamental electrochemical properties of MAX phases and the possible application of these compounds as (photo)electrocatalysts for energy conversion. 22,31,32 In previous studies, 33,34 MAX showed better catalytic performances when exposed to different light sources. Ta 2 AlC, Cr 2 AlC, Ti 2 AlC and Ti 3 AlC 2 demonstrated improved photoelectrocatalytic H 2 production when illuminated by a 660 nm light source.…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies have taken one step back, looking into the fundamental electrochemical properties of MAX phases and the possible application of these compounds as (photo)electrocatalysts for energy conversion. 22,31,32 In previous studies, 33,34 MAX showed better catalytic performances when exposed to different light sources. Ta 2 AlC, Cr 2 AlC, Ti 2 AlC and Ti 3 AlC 2 demonstrated improved photoelectrocatalytic H 2 production when illuminated by a 660 nm light source.…”
Section: Introductionmentioning
confidence: 91%
“…In each case, authors achieve, respectively, photocurrent values above 7 mAcm −2 (7% efficiency) and 10 mAcm −2 (12.82% efficiency). Currently stand out layered selenophosphites photocatalysts and improved Ag‐sensitized TiO 2 119‐125 . Photoelectrocatalysis report typical photoanodes of BiVO 4 and Ta 3 N 5 , with still low efficiency, and real pilot implementations with a short‐term 100 kg/day H 2 production 126‐128 …”
Section: Sun Heat and Electricity For Water Splitting‐based Hydrogen ...mentioning
confidence: 99%
“…Currently stand out layered selenophosphites photocatalysts and improved Ag-sensitized TiO 2 . [119][120][121][122][123][124][125] Photoelectrocatalysis report typical photoanodes of BiVO 4 and Ta 3 N 5 , with still low efficiency, and real pilot implementations with a short-term 100 kg/day H 2 production. [126][127][128]…”
Section: Photoelectrochemical Cells Based On Semiconductorsmentioning
confidence: 99%
“…However, halogenation of graphite (such as fluorination) is a unique approach that has been demonstrated to improve the electrochemical performance of graphite base electrodes , but yet to be examined in MAX phase materials. In light of this, our group have been demonstrated that many properties of graphene were triggered by fluorine doing including conductivity, specific capacity, electrochemical performance, and mechanical properties. ,, This diverse property allows fluorinated graphite in a wide range of applications such as sensors, , photocatalysts, energy storage, , photodetectors, field effect transistors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, our group have been demonstrated that many properties of graphene were triggered by fluorine doing including conductivity, specific capacity, electrochemical performance, and mechanical properties. 21,23,24 This diverse property allows fluorinated graphite in a wide range of applications such as sensors, 21,25 photocatalysts, 26 energy storage, 27,28 photodetectors, 29 field effect transistors, 30 and so on.…”
Section: ■ Introductionmentioning
confidence: 99%